2023
DOI: 10.3389/fimmu.2023.1284344
|View full text |Cite
|
Sign up to set email alerts
|

Histone lactylation regulates cancer progression by reshaping the tumor microenvironment

Junxing Qu,
Peizhi Li,
Zhiheng Sun

Abstract: As a major product of glycolysis and a vital signaling molecule, many studies have reported the key role of lactate in tumor progression and cell fate determination. Lactylation is a newly discovered post-translational modification induced by lactate. On the one hand, lactylation introduced a new era of lactate metabolism in the tumor microenvironment (TME), and on the other hand, it provided a key breakthrough point for elucidation of the interaction between tumor metabolic reprogramming and epigenetic modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 118 publications
0
5
0
Order By: Relevance
“…In 2019, Zhang et al [128] identified histone lysine lactylation (lactyl-amide conjugation) and protein lactylation as an effect of lactate accumulation able to introduce epigenetic changes and modify post-translational characteristics of some proteins. Since then, it was found that lactylation participates in many pro-tumoral hallmarks [129][130][131][132][133][134][135][136][137][138][139]. Interestingly, DCA is one of the drugs that can decrease/inhibit lactylation.…”
Section: Mechanism Of Action Of Dcamentioning
confidence: 99%
“…In 2019, Zhang et al [128] identified histone lysine lactylation (lactyl-amide conjugation) and protein lactylation as an effect of lactate accumulation able to introduce epigenetic changes and modify post-translational characteristics of some proteins. Since then, it was found that lactylation participates in many pro-tumoral hallmarks [129][130][131][132][133][134][135][136][137][138][139]. Interestingly, DCA is one of the drugs that can decrease/inhibit lactylation.…”
Section: Mechanism Of Action Of Dcamentioning
confidence: 99%
“…In 2019, Zhang et al [ 128 ] identified histone lysine lactylation (lactyl-amide conjugation) and protein lactylation as effects of lactate accumulation that are able to introduce epigenetic changes and modify the post-translational characteristics of some proteins. Since then, it was found that lactylation participates in many protumoral hallmarks [ 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ]. Interestingly, DCA is one of the drugs that can decrease/inhibit lactylation.…”
Section: The Pdh Complexmentioning
confidence: 99%
“…The activity of epigenetic modulators requires cellular metabolites; thus, understanding the interplay between epigenetics and metabolism in disease contexts is essential. For example, the tumor microenvironment in cancer vastly differs in its metabolic makeup compared with surrounding normal tissue ( Qu et al 2023 ), which could have a profound impact on the epigenetic modulators as a whole or selectively. Additionally, attention on RNA epigenetics and its role in stress, aging, metabolism, and immunology is a young but exciting field that will open future opportunities for discovery.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%